DNA mtCOI Barcodes for Maritime Biosecurity: A Proof of Concept in French Polynesia Ports - Garcia-Vazquez, Eva; Ardura, Alba; Planes, Serge (Frontiers in Ecology and Evolution, 2020)
DNA barcodes have been proposed for diverse applications as markers for species identification. One application that is not fully explored yet is their use for assessing the species biodiversity and presence of invasive alien species (IAS) in maritime biosecurity. The phylogeographical signals of the mitochondrial COI (mtCOI) gene have been sometimes used to infer the number of introductions and the origin of biological invasions. Here, we employed mtCOI barcodes of mollusks and acorn barnacles (N = 751) from ports of French Polynesia to infer the effect of port size, maritime traffic, and degree of openness in the risk of biological invasions. With 17.2% of non-indigenous species (NIS) recorded here, significant differences in diversity were found among docks and between long-time docked ships and their closest piers. A higher proportion of NIS was found from sheltered compared to open ports regardless of their size and traffic. Less frequent wave washing, a lower effect of currents, and partial isolation in sheltered ports could explain the difference. The results suggest that port biota surveys should focus first on ports sheltered from the open sea and emphasize the value of mtCOI barcodes for the early detection of potential invasive species and for prioritizing surveillance efforts.